Milk fat globule epidermal growth factor-8 limits tissue damage through inflammasome modulation during renal injury. Issue 5 (3rd June 2016) - Brissette, Marie-Joëlle; Laplante, Patrick; Qi, Shijie; Latour, Mathieu; Cailhier, Jean-Francois
Abstract : MFG-E8-reprogramming of macrophages has a protective role in UUO through inflammasome modulation, preventing severe tissue damage and fibrosis. Abstract: Mediators released by apoptotic renal resident cells play a crucial role in modification of the inflammatory microenvironment. We have demonstrated that milk fat globule epidermal growth factor 8 (MFG-E8) is released by apoptotic cells, which results in reduced proinflammatory cytokine production by macrophages. The present study was designed to study the role of MFG-E8 on the modulation of tissue damage and macrophage phenotype in a renal inflammatory model, unilateral ureteral obstruction (UUO). C57BL/6 WT or MFG-E8 KO mice underwent ureteral ligation for 3, 7, and 14 d to evaluate renal injury. MFG-E8 (30 µg/kg) or vehicle was also administered i.p. MFG-E8 administration reduced kidney damage and fibrosis compared with control, whereas its absence in MFG-E8 KO mice was associated with more severe disease. Moreover, MFG-E8 administration was associated with decreased inflammasome activation in the kidney. Furthermore, adoptive transfer of MFG-E8–stimulated macrophages reduced activation of inflammasome and tissue damage. In all cases, both the systemic administration of MFG-E8 and MFG-E8–treated macrophages promoted accumulation of anti-inflammatory CD206 + macrophages. We propose that the protective role of MFG-E8 is mediated through anti-inflammatory macrophage reprogramming which results in decreased inflammasome activation, preventing severe tissue damage. These data provide valuable insight for identification of MFG-E8 as a novel target in modulation of inflammatory diseases.